WEBVTT
00:00:00.110 --> 00:00:08.550
In this lesson, we’ll learn how to solve logarithmic equations involving logarithms with different bases.
00:00:09.740 --> 00:00:15.480
So, after this lesson, you should be able to find a solution set from an equation containing logarithms with different bases.
00:00:16.980 --> 00:00:19.210
And we can see here what the base is of a logarithm.
00:00:19.350 --> 00:00:22.250
So, we’ve got here the base and the argument both pointed out.
00:00:23.620 --> 00:00:28.560
However, before we get on and start to solve our logarithmic equations, there’s one thing that we want to recap.
00:00:28.710 --> 00:00:31.160
And that is how we change the base of a logarithm.
00:00:32.840 --> 00:00:36.810
Well, let’s think about what we’ve got here, and this is when we’re looking at changing the base of a logarithm.
00:00:36.910 --> 00:00:39.220
So, we’ve got log to the base 𝑎 of 𝑏.
00:00:40.980 --> 00:00:48.530
But what we have is the situation or a formula here that helps us change this to a logarithm with any base that we want.
00:00:49.220 --> 00:01:01.610
And that is that if we have log to the base 𝑎 of 𝑏, this can be equal to log to the base 𝑥 of 𝑏 over log to the base 𝑥 of 𝑎, where the base can be anything we want it to be.
00:01:02.050 --> 00:01:04.880
And we can see how that’s useful in a second cause I’ll show you an example.
00:01:06.290 --> 00:01:09.770
Well, let’s have a look at this example to see how this becomes useful.
00:01:10.130 --> 00:01:17.270
Well, if we’ve got log to the base nine of 27, then we can rewrite this using the formula that we’ve got on the left-hand side.
00:01:18.510 --> 00:01:23.680
So, this becomes log to the base something of 27 over log to the base something of nine.
00:01:23.680 --> 00:01:27.740
And we’ve got something because it’s up to us to decide what’s going to be useful.
00:01:29.310 --> 00:01:36.140
Well, if we take a look at 27 and nine, we can see that, in fact, both of these are three to the power of something.
00:01:36.140 --> 00:01:38.320
So we’ve got three to the power of three or three squared.
00:01:39.730 --> 00:01:48.050
So therefore, we could use three as our base because this can become very useful when we have a look at one of our log laws in a second to actually simplify what we have here.
00:01:49.090 --> 00:01:53.520
So what this is gonna give us is log to the base three of three cubed over log to the base three of three squared.
00:01:53.940 --> 00:01:56.850
And now obviously, we’ve changed the base of our logarithm here.
00:01:56.850 --> 00:01:59.470
But what I want to do is actually just show how we would simplify this.
00:01:59.760 --> 00:02:01.370
We do that by using our log rules.
00:02:02.630 --> 00:02:09.590
And the log rules we’re gonna use are that log to the base 𝑎 of 𝑚 to the power of 𝑛 equals 𝑛 log to the base 𝑎 of 𝑚.
00:02:10.120 --> 00:02:13.330
And also, log to the base 𝑎 of 𝑎 is equal to one.
00:02:14.730 --> 00:02:19.910
Well, using the first rule, we get three log to the base three of three over two log to the base three of three.
00:02:21.260 --> 00:02:26.360
Well, then, if you use the second rule, we see that log to the base three of three is just going to be one.
00:02:26.390 --> 00:02:31.540
So, we got three multiplied by one over two multiplied by one, which would give us three over two.
00:02:31.570 --> 00:02:39.810
So, what we’ve done is we’ve shown how we changed the base of a logarithm to help us simplify cause we’ve shown that log to the base nine of 27 would be equal to three over two.
00:02:40.410 --> 00:02:41.060
Okay, great.
00:02:41.300 --> 00:02:44.910
So now we’ve recaped some of the skills we’re gonna need to actually solve our equations.
00:02:45.010 --> 00:02:50.070
Let’s get on and look at some examples of how we solve equations using the changing of base of a logarithm.
00:02:51.640 --> 00:02:57.700
Find the solution set of log to the base three of 𝑥 equals log to the base nine of four in the set of real numbers.
00:02:58.810 --> 00:03:02.740
So to solve this problem, what we’re going to do is actually change the base of our logarithm.
00:03:02.740 --> 00:03:10.760
And we do that using this formula here, which is that log to the base 𝑎 of 𝑏 equals log to the base 𝑥 of 𝑏 over log to the base 𝑥 of 𝑎.
00:03:12.230 --> 00:03:17.060
And in our problem, we’re only going to change the base of the logarithm on the right-hand side of the equation.
00:03:17.060 --> 00:03:25.120
And that’s because we’re gonna keep it as log to the base three on the left-hand side because that’s what we’re gonna change the base number to with our right-hand logarithm.
00:03:25.940 --> 00:03:32.910
Well, when we do this, we get log to the base three of 𝑥 equals log to the base three of four over log to the base three of three squared.
00:03:32.910 --> 00:03:39.830
And what I’ve done here is actually changed our nine into three squared because this, in fact, is the reason why we wanted to have the base of three.
00:03:39.930 --> 00:03:45.060
And that’s because we can actually use one of our log rules or a couple of our log rules to actually help us simplify.
00:03:46.400 --> 00:03:52.480
Well, the first rule we’re gonna use is that log to the base 𝑎 of 𝑚 to the power of 𝑛 is equal to 𝑛 log to the base 𝑎 of 𝑚.
00:03:52.780 --> 00:03:58.440
So, we’re gonna get log to the base three of 𝑥 equals log to the base three of four over two log to the base three of three.
00:04:00.000 --> 00:04:04.090
So now what we do is apply another log rule, which tells us that log to the base 𝑎 of 𝑎 equals one.
00:04:04.090 --> 00:04:09.080
And when we do that, we get log to the base three of 𝑥 is equal to log to the base three of four over two.
00:04:09.320 --> 00:04:12.710
That’s because we had two multiplied by one because log to the base three of three was one.
00:04:14.260 --> 00:04:16.120
So now what we can do is multiply each side by two.
00:04:16.150 --> 00:04:19.700
And when we do that, we get two log to the base three of 𝑥 equals log to the base three of four.
00:04:21.050 --> 00:04:29.850
Well, now, if we actually apply our first rule, but in reverse, we can actually rearrange the left-hand side to be log to the base three of 𝑥 squared equals log to the base three of four.
00:04:30.140 --> 00:04:40.240
And the reason we want to do this is cause now what we can do is actually equate our arguments because we see that we’ve got log to the base three and then of 𝑥 squared and log to the base three of four.
00:04:41.700 --> 00:04:44.530
So therefore, when we do that, we’re gonna get 𝑥 squared equals four.
00:04:46.100 --> 00:04:49.840
And then when we take the square root of this, we’re gonna get 𝑥 is equal to two.
00:04:50.540 --> 00:04:51.440
But you might think, “Well, hold on!
00:04:51.440 --> 00:04:55.290
What about the negative value, because shouldn’t we have negative two or two?”
00:04:57.180 --> 00:04:59.700
Well, in fact, we’re not interested in the negative value.
00:04:59.700 --> 00:05:06.120
And that’s because what we know is that the argument of a logarithm must be positive and not equal to one.
00:05:06.700 --> 00:05:14.370
And as we’re looking to find 𝑥, which is, in fact, the argument of the logarithm on the left-hand side, we can’t have a negative value.
00:05:15.760 --> 00:05:19.720
So therefore, we can say that the solution set of our equation is going to be two.
00:05:21.120 --> 00:05:21.720
Okay, great.
00:05:21.720 --> 00:05:23.300
So that’s our first equation solved.
00:05:23.830 --> 00:05:25.300
But here, we did mention something.
00:05:25.330 --> 00:05:29.030
We mentioned that the argument of a logarithm must be positive and not equal to one.
00:05:29.550 --> 00:05:30.290
But why is that?
00:05:30.290 --> 00:05:31.620
Well, let’s take a quick look.
00:05:32.680 --> 00:05:39.750
So, as we said, if we’ve got log to the base 𝑎 of 𝑏, then we’d say that 𝑏 must be positive and not equal to one.
00:05:40.370 --> 00:05:41.340
But why is this?
00:05:42.770 --> 00:05:45.170
And you might actually apply some logic and go, “Well, hold on.
00:05:45.790 --> 00:05:52.730
If log to the base 𝑎 of 𝑏 is equal to 𝑥, then we know that 𝑎 to the power of 𝑥 is gonna be equal to 𝑏.”
00:05:54.090 --> 00:05:56.120
Well, 𝑏 can be clearly be negative.
00:05:56.560 --> 00:05:58.680
That’s because here’s an example showing it.
00:05:58.760 --> 00:06:03.960
If we had negative three all cubed, then this would give us a result of negative 27.
00:06:04.550 --> 00:06:07.240
So why can’t 𝑏 be a negative value?
00:06:07.730 --> 00:06:10.930
Well, in fact, it’s not actually the argument that we need to look at.
00:06:11.480 --> 00:06:18.980
It’s the base, because this is what is our limiting factor and gives us our domain for the possible values for our argument.
00:06:20.150 --> 00:06:22.840
Well, in fact, we know that a base cannot be negative.
00:06:22.840 --> 00:06:26.820
And what we’re gonna do is use this example to highlight why.
00:06:27.290 --> 00:06:40.050
So if we had log to the base negative two of 𝑥 equals a half, well, then what we’d have if we actually put it into our exponent form is negative two to the power of a half equals 𝑥.
00:06:41.100 --> 00:06:44.800
So then if we wanted to solve this for 𝑥, we’d have to take the square root of negative two.
00:06:44.830 --> 00:06:47.550
And that’s because power of a half is the same as square root.
00:06:47.550 --> 00:06:51.390
So we’d have the square root of negative two is equal to 𝑥, which we know is undefined.
00:06:51.550 --> 00:06:55.130
So therefore, that shows why we cannot have a negative base.
00:06:56.460 --> 00:07:02.450
And therefore, following from this, if we can’t have a negative base, then we cannot have a negative argument.
00:07:02.810 --> 00:07:05.520
So that shows why it cannot be negative.
00:07:06.810 --> 00:07:12.010
So we’re also gonna show why it cannot be the value of one, and that’s because the base cannot be of value one.
00:07:12.010 --> 00:07:20.920
And that’s because let’s, for instance, think if we had log to the base one of two is equal to 𝑎, then if we rearrange this it’d be one to the power of 𝑎 equals two.
00:07:21.220 --> 00:07:24.850
Well, this can’t happen because one to the power of anything is just one.
00:07:24.930 --> 00:07:27.080
And we’re seeing the same with the example below.
00:07:27.350 --> 00:07:28.080
Okay, great.
00:07:28.420 --> 00:07:32.990
So we now know why the argument of a logarithm must be positive and not equal to one.
00:07:33.280 --> 00:07:35.140
So let’s get on and solve some more problems.
00:07:37.060 --> 00:07:46.910
Determine the solution set of the equation log to the base three of 𝑥 plus log to the base 243 of 𝑥 to the power of five plus three equals zero in the set of real numbers.
00:07:48.250 --> 00:07:57.000
So to solve this problem, what we’re gonna do is use our change of base formula, which we’ve got, which is log to base 𝑎 of 𝑏 equals log to the base 𝑥 of 𝑏 over log to the base 𝑥 of 𝑎.
00:07:58.240 --> 00:08:07.710
So if we take a look at our problem, or our equation, then what we’re gonna do is we’re gonna use this change of base formula on log to the base 243 of 𝑥 to the power of five.
00:08:07.920 --> 00:08:15.330
And we’re gonna use it on this because actually what we want to do is change the base to log to the base three so we’ve got each of our logarithms with the same base.
00:08:16.610 --> 00:08:26.520
So when we do this, what we’re gonna get is log to the base three of 𝑥 plus log to the base three of 𝑥 to the power of five over log to the base three of 243 plus three is equal to zero.
00:08:26.520 --> 00:08:31.450
And this is because we can decide what the base is when we’re changing the base.
00:08:32.760 --> 00:08:38.210
And the reason this is gonna be useful is because we know that 243 is three to the power of five.
00:08:39.410 --> 00:08:43.760
So now what we’re gonna do is use this in a couple of our log laws to help us simplify our equation.
00:08:44.350 --> 00:08:53.120
The laws we’re gonna look at is log to the base 𝑎 of 𝑚 to the power of 𝑛 is equal to 𝑛 log to the base 𝑎 of 𝑚 and log to the base 𝑎 of 𝑎 is equal to one.
00:08:54.330 --> 00:09:06.960
So when we apply these, what we’re gonna get is log to the base three of 𝑥 is equal to five log to the base three of 𝑥, and that’s because we use our first rule for that one, and then divided by five log to the base three of three.
00:09:07.310 --> 00:09:10.830
And that’s because, as we said, 243 was the same as three to the power of five.
00:09:10.830 --> 00:09:13.960
So then we put the five in front of the log to the base three.
00:09:14.160 --> 00:09:18.120
So we’ve got five log to the base three of three, then plus three equals zero.
00:09:19.360 --> 00:09:21.750
Well, we know that log to the base three of three is one.
00:09:22.320 --> 00:09:25.230
So therefore, we’re just gonna have five multiplied by one on the denominator.
00:09:26.300 --> 00:09:33.960
So then what we’re gonna do is divide through by five as well, which is gonna give us two log to the base three of 𝑥 plus three equals zero.
00:09:33.960 --> 00:09:37.700
And that’s cause we had log to the base three of 𝑥 and then plus log to the base three of 𝑥.
00:09:37.700 --> 00:09:38.820
So that gives us two of those.
00:09:40.130 --> 00:09:46.640
So then what we’re gonna do is subtract three from each side of the equation, which is gonna give us two log to base three of 𝑥 equals negative three.
00:09:47.840 --> 00:09:49.940
Well, then, what we’ve got is a little trick to help us.
00:09:50.120 --> 00:09:54.980
And that is that we can turn the right-hand side into something in log to the base three.
00:09:55.370 --> 00:10:01.210
And we could do that because negative three would be the same as negative three multiplied by log to the base three of three.
00:10:02.470 --> 00:10:06.540
So therefore, we’ve got two log to the base three of 𝑥 equals negative three log to the base three of three.
00:10:07.900 --> 00:10:11.190
So then what we can do is apply the converse of our first rule.
00:10:11.540 --> 00:10:17.220
So we can have log to the base three of 𝑥 squared equals log to the base three of three to the power of negative three.
00:10:18.360 --> 00:10:22.220
Well, because our base is the same, what we can do now is equate our arguments.
00:10:23.060 --> 00:10:26.160
So we get 𝑥 squared is equal to three to the power of negative three.
00:10:27.470 --> 00:10:31.100
So therefore, 𝑥 squared is gonna be equal to one over 27.
00:10:32.200 --> 00:10:37.510
Well, then, if we take the square root of both sides, what we’re gonna get is 𝑥 is equal to one over root 27.
00:10:37.930 --> 00:10:42.690
We’re not interested in the negative value because we’re told that we only want to find the set of real numbers.
00:10:42.690 --> 00:10:50.030
And this is because 𝑥 is, in fact, the argument in two of our logarithms, and an argument has to be positive and cannot be equal to one.
00:10:50.030 --> 00:10:56.250
Well, then what we’re gonna do is simplify our root 27 by using one of our radical or surd rules.
00:10:56.550 --> 00:11:01.710
And that is that root 27 is same as root nine multiplied by root three, which gives us three root three.
00:11:02.760 --> 00:11:08.420
So therefore, we can say that the solution set for our equation is one over three root three.
00:11:10.500 --> 00:11:13.570
So great, we’ve actually solved this problem with an equation.
00:11:13.690 --> 00:11:16.190
So now, let’s take a look at one that involves a quadratic.
00:11:18.510 --> 00:11:26.120
Find the solution set of log to the base two of 𝑥 equals log to the base four of three 𝑥 plus 28 in the set of real numbers.
00:11:27.660 --> 00:11:31.000
So in this problem, what we can do is use the change of base formula.
00:11:31.030 --> 00:11:35.260
So log to the base 𝑎 of 𝑏 equals log to the base 𝑥 of 𝑏 over log to the base 𝑥 of 𝑎.
00:11:35.260 --> 00:11:40.900
And we’re gonna use it because what we want to do is have the right-hand side with same base as the left-hand side.
00:11:42.880 --> 00:11:50.060
So when we do that, what we’re gonna get is log to the base two of 𝑥 equals log to the base two of three 𝑥 plus 28 over log to the base two of four.
00:11:51.550 --> 00:11:58.910
And whenever we’re solving a problem like this, what we do look out for is where we could actually have something where we’ve got, for instance, log to the base two of two.
00:11:59.390 --> 00:12:01.770
So it’s the same as the form log to the base 𝑎 of 𝑎.
00:12:01.770 --> 00:12:05.940
And in fact, we can have that here because four is the same as two squared.
00:12:07.570 --> 00:12:12.220
So we can rewrite it as our denominator, being log to the base two of two squared.
00:12:13.570 --> 00:12:16.940
So now, to simplify further, what can do is apply a couple of our log rules.
00:12:17.440 --> 00:12:22.200
First is that log to the base 𝑎 of 𝑚 to the power of 𝑛 is equal to 𝑛 log to base 𝑎 of 𝑚.
00:12:22.620 --> 00:12:25.230
And then, we’ve got log to base 𝑎 of 𝑎 equals one.
00:12:26.800 --> 00:12:33.860
So applying the first rule, we’ve got log to the base two of 𝑥 equals log to the base two of three 𝑥 plus 28 over two log to the base two of two.
00:12:35.370 --> 00:12:43.630
And then applying the second rule, we can say that the denominator becomes just two because it’s two multiplied by one, as log to the base two of two is just one.
00:12:45.470 --> 00:12:51.600
So then, if we multiply both sides by two, we get two log to the base two of 𝑥 equals log to the base two of three 𝑥 plus 28.
00:12:52.200 --> 00:12:57.980
So now what we’re gonna do is take a look at the left-hand side and apply the converse of the first rule we looked at for our logarithms.
00:12:59.480 --> 00:13:05.210
And when we do that, we get log to the base two of 𝑥 squared equals log to the base two of three 𝑥 plus 28.
00:13:05.700 --> 00:13:11.940
So now what we can do is actually equate our arguments because we have the log to the same base on either side of the equation.
00:13:13.330 --> 00:13:17.300
So when we do that, we now have 𝑥 squared equals three 𝑥 plus 28.
00:13:17.810 --> 00:13:22.060
So now what we can do is rearrange to actually change this into a quadratic that’s equal to zero.
00:13:22.060 --> 00:13:25.680
So we’re gonna subtract three 𝑥 and subtract 28 from each side.
00:13:26.820 --> 00:13:30.480
So, when we do that, we get the quadratic 𝑥 squared minus three 𝑥 minus 28 equals zero.
00:13:30.800 --> 00:13:32.870
So now, what we need to do is solve this for 𝑥.
00:13:33.980 --> 00:13:38.290
So, if we want to solve 𝑥 squared minus three 𝑥 minus 28 equals zero, what we’re gonna do is factor it.
00:13:39.580 --> 00:13:44.750
So, if we factor this quadratic, we’re gonna get 𝑥 minus seven multiplied by 𝑥 plus four equals zero.
00:13:46.190 --> 00:13:49.930
So therefore, we get 𝑥 is equal to seven or negative four.
00:13:50.450 --> 00:13:54.170
So our solution set then is gonna be seven or negative four, isn’t it?
00:13:55.450 --> 00:13:57.890
Well, no because 𝑥 cannot be one of our values.
00:13:58.280 --> 00:14:00.570
The value it can’t be is negative four.
00:14:01.090 --> 00:14:07.160
And that’s because we know that if we take a look back at our equation, 𝑥 is the argument of the left-hand side.
00:14:07.160 --> 00:14:11.350
And we know that the argument must be positive and not equal to one.
00:14:12.580 --> 00:14:15.420
So therefore, the solution set of our equation is just seven.
00:14:17.150 --> 00:14:19.110
Okay, so there we solved a problem with quadratic.
00:14:19.110 --> 00:14:24.660
What we’re gonna do now is move on to a problem where, in fact, we’re gonna have more than one result in our set.
00:14:26.680 --> 00:14:34.560
Solve log to the base two of log to the base three of 𝑥 squared minus eight 𝑥 equals one where 𝑥 is in the set of real numbers.
00:14:35.550 --> 00:14:40.390
So the first thing we can do with this problem is make sure that we’ve got a log to the same base on each side of the equation.
00:14:40.390 --> 00:14:42.670
And we can do that by applying one of our log rules.
00:14:42.700 --> 00:14:45.140
And that is that log to the base 𝑎 of 𝑎 equals one.
00:14:46.440 --> 00:14:58.030
So, therefore, we can say that log to the base two of log to the base three of 𝑥 squared minus eight 𝑥 equals log to base two of two because, as we said, one is just the same as log to the base two of two.
00:14:58.510 --> 00:15:03.570
So now the reason we’ve done this is because what we’ve got is log to the same base on the left- and right-hand sides.
00:15:03.850 --> 00:15:06.440
So, what we can do is equate our arguments.
00:15:07.530 --> 00:15:11.590
So, we can say that log to the base three of 𝑥 squared minus eight 𝑥 is equal to two.
00:15:12.980 --> 00:15:18.430
So now, to solve for 𝑥, what we can do first is actually rearrange from logarithmic to exponent form.
00:15:18.460 --> 00:15:22.980
So if we have log to the base 𝑎 of 𝑏 equals 𝑥, then we say that 𝑎 to the power of 𝑥 is gonna be equal to 𝑏.
00:15:24.130 --> 00:15:35.950
So therefore, if we identify our 𝑎, 𝑏, and 𝑥, well then we can rewrite our equation as three squared equals 𝑥 squared minus eight 𝑥, which is gonna give us nine equals 𝑥 squared minus eight 𝑥.
00:15:37.150 --> 00:15:39.650
So then, what we’re gonna do is subtract nine from each side of the equation.
00:15:39.650 --> 00:15:42.920
So, we get zero equals 𝑥 squared minus eight 𝑥 minus nine.
00:15:43.440 --> 00:15:45.310
So now what we need to do is solve this quadratic.
00:15:46.140 --> 00:15:47.730
Well, we can solve the quadratic by factoring.
00:15:47.730 --> 00:15:51.280
And if we do, we get zero equals 𝑥 minus nine multiplied by 𝑥 plus one.
00:15:52.580 --> 00:15:55.500
So therefore, we can say that 𝑥 is gonna be equal to nine or negative one.
00:15:55.530 --> 00:15:57.950
So great, and these both are going to be in our solution set.
00:15:59.350 --> 00:16:05.280
Well, you might think, “Well, no, it can’t be because we know that the argument must be positive and not equal to one.”
00:16:05.700 --> 00:16:07.610
So therefore, we cannot have the negative value.
00:16:08.130 --> 00:16:14.000
However, that is not the case in this particular problem because if we take a look at the argument, the argument is not 𝑥.
00:16:14.420 --> 00:16:19.610
The argument is 𝑥 squared minus eight 𝑥, well, the argument of one of our logarithms.
00:16:20.910 --> 00:16:26.280
And what we’re gonna do to show that is actually substitute in 𝑥 equals negative one into this argument.
00:16:27.210 --> 00:16:36.360
Well, if we do that, we get negative one all squared minus eight multiplied by negative one, which is gonna give us one plus eight because negative one squared is just one.
00:16:36.650 --> 00:16:39.730
And if you subtract a negative, it’s the same as adding a positive.
00:16:40.590 --> 00:16:44.980
Well, this gives us the value of nine, which is both positive and not equal to one.
00:16:45.350 --> 00:16:48.840
So therefore, it satisfies the conditions that we have for our argument.
00:16:50.050 --> 00:16:55.580
So therefore, we can say that the solution set for our equation is nine and negative one.
00:16:57.590 --> 00:16:58.130
Okay, great.
00:16:58.130 --> 00:16:59.560
We’ve looked at a range of different problems.
00:16:59.730 --> 00:17:02.620
So now, let’s take a look at a summary of the key points.
00:17:03.510 --> 00:17:16.040
So, if we take a look at our key points, the first one is that if we want to change the base of one of our logarithms, then we can say that the log to the base 𝑎 of 𝑏 is equal to the log to the base 𝑥 of 𝑏 over the log to the base 𝑥 of 𝑎.
00:17:16.250 --> 00:17:18.890
So, we can actually have the base changed to anything that we want.
00:17:19.950 --> 00:17:26.230
And what we tend to do is choose a base that’s gonna be the most useful when we’re looking to solve an equation or simplify an expression.
00:17:27.670 --> 00:17:34.300
Then what we also looked at is that if we have log to the base 𝑎 of 𝑏, then the 𝑏 would be our argument and the 𝑎 would be our base.
00:17:35.430 --> 00:17:37.610
And the argument must be positive and equal to one.
00:17:37.670 --> 00:17:43.510
And in fact, this is because the base must also be a positive value, not equal to one or zero.
00:17:44.620 --> 00:17:53.500
And this is important because we need to use this when considering the domain of 𝑥 if 𝑥 is part of an argument of a logarithm in an equation that we’re trying to solve.